Military Service and the Integration of Jews into the Roman Empire - González-Salinero, Raúl, (The Brill Reference Library of Judaism ;, 2022)
"According to Raúl González Salinero, the plurality of religious expressions within Judaism prior to the predominance of the rabbinical current disproves the assumption according to which some Jewish customs and precepts (especially the Sabbath) prevented Jews from joining the Roman army without renouncing their ancestral culture. The military exemption occasionally granted to the Jews by the Roman authorities was compatible with their voluntary enlistment (as it was in the Hellenistic armies) in order to obtain Roman citizenship. As the sources attest, Judaism did not pose any insurmountable obstacle to integration of the Jews into the Roman world. They achieved a noteworthy presence in the Roman army by the fourth century CE, at which time the Church's influence over imperial power led to their exclusion from the militia armata"--